Development of E-Modules Based on Character Education: Logic Subjects - Kiik, Blasius; Simbolon, Naeklan; Panjaitan, Keysar (RIRAI Publisher, 2024)
Character education-based e-modules are an innovation in education that aims to increase the effectiveness of learning and expand accessibility to subject matter by integrating positive values and attitudes in students. Currently, the Logic Learning Module at SMA Satu Padu Boarding School-Tiga Juhar still uses a conventional approach without integrating character education values and has not adopted online learning. This research aims to evaluate the feasibility and effectiveness of developing an e-module based on character education for class XI students in the Logic subject at SMA Satu Padu Boarding School-Tiga Juhar. The research method used was research and development (R&D), with research subjects totaling 19 class XI students. The object of this research is the Basics of Logic material. The research stages include validation tests by material experts, media experts, and design experts, as well as individual and group trials on the use of character-based e-modules. This research also tests the effectiveness of e-modules based on character education. The research results show that students who use e-modules based on character education are